Answer:
x = 2
y = - 1
Explanation:
5x/6 + y/3 = 4/3
2x/3 - y/2 = 11/6
Multiply the above equation by 6 to express in linear form
6 × (5x/6 + y/3 = 4/3)
5x + 2y = 8.... (1)
6 × (2x/3 - y/2 = 11/6)
4x - 3y = 11.... (2)
Thus, the equation are:
5x + 2y = 8.... (1)
4x - 3y = 11.... (2)
Next, multiply equation (1) by 3 and equation (2) by 2. This is illustrated below:
3 × (5x + 2y = 8)
15x + 6y = 24 ..... (3)
2 × (4x - 3y = 11)
8x - 6y = 22 ... (4)
Next, add equation 3 and 4 together. This is illustrated below:
.. 15x + 6y = 24... (3)
+ 8x - 6y = 22 .... (4)
¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯
23x = 46
Divide both side by 23
x = 46/23
x = 2
Next, substitute the value of x into any of the equation. Here, we shall substitute the value of x into equation (3). This is illustrated below:
15x + 6y = 24... (3)
x = 2
15(2) + 6y = 24
30 + 6y = 24
Collect like terms
6y = 24 - 30
6y = - 6
Divide both side by 6
y = - 6/6
y = - 1
Therefore, the value of x and y is
x = 2
y = - 1